Comportamiento asociado al consumo de alcohol en espacios públicos de la ciudad de Loja. - Iñiguez Arias, Nadia Cristina (2015)
This research entitled: associated with the consumption of alcohol in public spaces in the city of Loja behavior, aims to identify the different behaviors associated with alcohol consumption in public spaces of the city of Loja, the focus of the research is mixed, quantitative ethnographic and qualitative research method. The instruments used for data collection were observation and interview in public places of the city of Loja, so the location, characterization of the preferred alcohol consumption sites, and determination of behavior was achieved aggressive and antisocial alcohol product. The preferred drink alcoholic beverages in public spaces sector are Zamora citadel, better known as "Pool" and the square of St. Sebastian being the predominant leisure reason for conducting this activity, which carries with aggressive and antisocial behaviors that endanger the integrity of individuals and the same physical spaces in which they find themselves